Antecedents of cloud enterprise resources planning implementation and their effects on business financial performance through competitive advantage - Olakunle, Jayeola (2022)
Cloud computing (CC) is recognised as a disruptive technology capable of providing competitive advantage and improved performance to firms. However, Malaysian SMEs are still slow in implementing CC despite numerous government supports. In addition, the impact of implementing CC on the performance of firms remains controversial. Therefore, this study aims to examine the relevance of government financial support (GFS) in conjunction with two chosen antecedents of cloud computing (CC) implementation in Malaysian manufacturing SMEs, namely feature-task match (FTM) and top management support on change management (TMSCM) which are supported by Technology-Organisation-Environment (TOE), Task-technology Fit (TTF), Kotter’s change management theories. Further, the study also examined the financial performance effect of CC implementation of Malaysian manufacturing SMEs directly and indirectly through competitive advantage (CA) with the support from the strategic management Resource-based view (RBV). A set of Google Forms questionnaire related to the implementation of cloud computing (CC) were sent to the owners and top-level managers of manufacturing SMEs in Selangor, Kuala Lumpur and Johor through emails. A total of 204 responses were usable for analysis and hypothesis testing. Statistical Package for the Social Sciences (SPPSS) version 25 and Structural Equation Modelling (SEM) using SMARTPLS 3.3.2 were used to analyse the collected data. Findings show that feature-task match (FTM), top management support on change management (TMSCM) and government financial support (GFS) are valid predictors of cloud computing (CC) implementation. However, GFS only negatively moderates the relationship between TMSCM and CC implementation, while it does not moderate the FTM and CC implementation relationship. Additionally, GFS only impacts financial performance through the mediation of CC implementation. Finally, CC implementation significantly improves financial performance both directly and indirectly through competitive advantage (CA). This research makes contribution to the current body of literature by integrating several theoretical frameworks (such as TOE, TTF, Kotter’s change management model and RBV) to develop a comprehensive model for ii understanding relevant factors of CC implementation, feature-task match (FTM), top management support on change management (TMSCM) and government financial support (GFS) which were under-researched in the previous studies. Furthermore, this study empirically provides evidence that deepens insights into how environmental factor (GFS) of the TOE acts as a pull factor that dampens the positive influence of TMSCM on CC implementation. Finally, based on the RBV, this study extends prior understandings by showing the financial performance impact of CC implementation through CA. This study also discusses some implications for practitioners and policy makers to promote and sustain SMEs’ CC implementation.